Inventory control and profitability in a hardware company in Manantay - Peru - Pizzan-Tomanguillo, Nieves del Pilar (2022)
The present investigation had as general objective: To determine the level of relationship between inventory control and profitability in the company "El mundo de los Repuestos JR E.I.R.L.", Period 2018-2019. Regarding the methodological structure of the study, they were: a basic quantitative approach, a correlational descriptive level, a non-experimental design with a longitudinal cut, a sample determined by 48 financial statements (24 financial statements and 24 income statements) monthly. of the company, the technique used was documentary analysis. It was concluded that there is a relationship between inventory turnover and return on assets, because a p-value = 0.027 <0.05 was found, as well as, there is a relationship between inventory turnover and net profitability, because a p-value = 0.048 <0.05, on the contrary, there is no relationship between inventory turnover and return on equity. Consequently, there is a relationship between average life time and net profitability, because a p-value = 0.00 <0.05 was found, and there is also a relationship between average life time and return on assets, because a p-value = 0.005 < 0.05, finally, there is a relationship between the average term of existence and the return on capital, because in table 9, a p-value = 0.008 <0.05 was found.